Bank Fragility and International Capital Mobility - Detragiache, Enrica (IMF Working Papers; Working Paper ;, 1999)
The paper examines the effects of increased financial integration on the economy and, specifically, the welfare of depositors and the business sector. A simple model of a small open economy with a fragile banking sector and imperfect capital mobility is developed. Increased international integration of the market for bank deposits makes runs on banks more likely and unambiguously hurts the domestic business sector. Depositors may gain or lose depending on the parameters. Even when depositors gain, the overall effect on the economy depends on the size of foreign assets held relative to the costs of bank crises.